Teaching and Research: A Way to Achieve Excellence at Higher Education - Mushtaq, Sara; Ramzan, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
The core objective of the research was to explore the relationship among teaching and research in order to achieve academic excellence at higher education. Quantitative type of data was collected from the Ph.D. and M.Phil. research students from eight universities of Punjab, comprising three faculties of Arts/Humanities, Science and Social Science. Study was descriptive in nature and survey method was adopted for the collection of data. Six departments namely English, Urdu, Chemistry, Physics, Education and Psychology from three faculties were selected through purposive sampling technique respectively. A self-developed questionnaire was used for the purpose of data collection. Questionnaire contained seven factors namely; Teacher as knowledge producer, Teacher role in content selection, Practical and pedagogical skills of teacher, Critical thinking and Problem-solving skills of teacher, Evaluation, Students participation in research and Impact of research to check the collaboration of research and teaching at higher education. Statistical Package for Social Sciences (SPSS) version 20 was used for analyzing the collected data. Correlation and Regression tests were applied to explore the relationship between teaching and research to attain academic excellence. Result of the study revealed that strong positive correlation was observed among ‘teacher as knowledge producer’ and ‘pedagogical skills of teachers’ and overall strong positive correlation exists between all the mentioned factors of teaching and research at university level. Results regarding the impact of research on quality of teaching explained the variation, one unit increase in research will cause 58% increase in quality of teaching and overall positive linear association was observed among research and teaching factors. Study highlighted that both (teaching and research) strengthen each other and considered obligatory to attain academic proficiency and quality education at university level.